2019
DOI: 10.1039/c8nr08936a
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte–mimicking Pluronic–lipid nanovesicle hybrids inhibit the growth and metastasis of breast cancer

Abstract: We have constructed a novel biomimetic Pluronic-lipid nanovesicle hybrid that mimics leukocytes, to target breast cancer and suppress metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…These observation was in line with previous reports that FA modified in the NLC mediated the cellular uptake of the DDS through the corresponding receptor, which was beneficial for cancer therapy. 32 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…These observation was in line with previous reports that FA modified in the NLC mediated the cellular uptake of the DDS through the corresponding receptor, which was beneficial for cancer therapy. 32 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the functional mechanism of the ceRNA network, we established a PPI regulation network, and selecting six hub genes, containing DGAT2, ACSL1, ADIPOQ, LPL, LEP, PCK1. Previous studies have shown that ve genes (DGAT2, ACSL1, ADIPOQ, LPL, and LEP) play important roles in the carcinogenesis of BC [23][24][25][26][27]. However, the relationship between PCK1 and BC has not been investigated, and the correlation between these hub genes and circRNAs in BC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In another attempt, Chen et al have reported developing a leukocyte-mimetic platform for PTX delivery to breast cancer to inhibit its growth and metastasis. [133] First, they fabricated lipid vesicles based on a mixture of phosphorylcholine lipids and pluronic P123 that contained PTX. Then, the membrane proteins from murine Mϕ cell line J774A.1 were incorporated in the vesicles via extrusion following a thin layer evaporation (TLE) procedure (Figure 14a).…”
Section: Biomedical Application Of Extracted Proteins or Whole Plasmamentioning
confidence: 99%